REVIEWS OF CLOUD COMPUTING FOR EDUCATION: SERVICES AND BENEFITS - King, Ting Sie (PEOPLE: International Journal of Social Sciences, 2015)
Cloud computing has become popular in the academic sector and has attracted the attention of academe, more specifically instructor and student. In this paper, the author reviews the cloud computing technology used in education and impact of the services on student learning and various educational potential of cloud-based tools and services for exploitation in teaching and learning are studied.